Pre-bloom application of gibberellin in ‘Tamnara’ grape increases γ-aminobutyric acid (GABA) production at full bloom - Jung, Chan Jin; Hur, Youn Young; Moon, Jin Seok; Jung, Sung-Min (Horticulture, environment and biotechnology, 2017)
A pre-bloom application of gibberellin (GA) on grapevines ( Vitis spp.) induces fruit set without fertilization (parthenocarpy) by inhibiting pollen tube growth. In the present study, we analyzed transcriptional changes in the Vitis γ-aminobutyric acid (GABA) metabolic genes and the levels of GABA in grapevines with or without GA treatment to understand how GA induces parthenocarpy in grapevines. Four Vitis glutamate decarboxylases (VvGAD), two GABA transaminases (VvGABA-T), and three succinic semialdehyde dehydrogenases (VvSSADH) were identified in grapevines, and their expression patterns were analyzed during inflorescence development from 14 days before full bloom (DBF) to 5 days after full bloom (DAF). Without GA treatment, we observed simultaneously high expression levels of VvGAD1 and VvGABA-T2 , with low levels of GABA from 10 to 5 DBF. With GA application, the levels of GABA were mostly unaltered, and the expression levels of VvGAD1 and VvGABA-T2 were around 30% lower compared to the plants without GA treatment at 12 DBF. However, at near full bloom in the plants treated with GA, GABA levels increased more than two-fold and VvGAD1 was upregulated. These results indicate that GABA levels are tightly regulated by VvGAD1 and VvGABA-T2 before pollination and that application of GA alters the pattern of GABA accumulation at near full bloom. This is the first report to describe how treatment with GA disrupts the crosstalk between the pistil and pollen via changes in GABA metabolism during GA-mediated parthenocarpic fruit initiation.